Association of Patient Sex and Pregnancy Status With Naloxone Administration During Emergency Department Visits - Forbes, Lauren A. (Obstet Gynecol, 2021)
OBJECTIVE: To evaluate the association of sex and pregnancy status with rates of naloxone administration during opioid overdose-related emergency department (ED) visits using the Nationwide Emergency Department Sample (NEDS). METHODS: A retrospective cohort study was conducted using NEDS 2016 and 2017 datasets. Eligible records included men and women, 15–49 years of age, with an opioid overdose-related ED visit; records for women were stratified by pregnancy status (ICD-10 O codes). A multivariable logistic regression model was used to assess the primary outcome of naloxone administration (CPT code: J2310). Secondary outcomes included subsequent admission and mortality. A subgroup analysis compared pregnant women who did versus did not receive naloxone. RESULTS: Records from 443,714 men, 304,364 non-pregnant women, and 25,056 pregnant women were included. Non-pregnant women had lower odds for naloxone administration (1.70% vs 2.10%; aOR: 0.86(0.83–0.89)) and mortality (2.21% vs 2.99%; aOR: 0.71(0.69–0.73)) but higher odds of subsequent admission (30.22% vs 27.18%; aOR: 1.04(1.03–1.06)) compared with men. Pregnant women had lower odds for naloxone administration (0..27% vs 1.70%; aOR: 0.16(0.13–0.21)) and mortality (0.41% vs 2.21%; aOR: 0.28(0.23–0.35)) but higher odds of subsequent admission (40.50% vs 30.22%; aOR: 2.04(2.00–2.10)) compared with non-pregnant women. Pregnant women who received naloxone had higher odds of mortality (14% vs 0.39%; aOR: 6.30(2.11–18.78)) compared with pregnant women who did not receive naloxone. Pregnant women who did not receive naloxone were more likely to have Medicaid as their expected insurance payer, be in the lowest quartile of median household income for residence ZIP code, and have a concurrent mental health diagnosis compared with pregnant women who did receive naloxone. CONCLUSION: Reproductive-aged non-pregnant and pregnant women were less likely to receive naloxone during opioid overdose-related ED visits compared to reproductive-aged men. Naloxone administration for reproductive-aged women should be prioritized in the efforts to reduce opioid- and pregnancy-related morbidity and mortality in the United States.